Expedient synthesis of functional single-component glycoliposomes using thiol–yne chemistry. Issue 23 (31st May 2016) - Goyard, D.; Shiao, T. C.; Fraleigh, N. L.; Vu, H.-Y.; Lee, H.; Diaz-Mitoma, F.; Le, H.-T.; Roy, R.
Abstract : The preparation of a set of eight unprecedented amphiphilic neoglycolipids forming liposome nanoparticles is reported. Abstract : The preparation of a set of eight unprecedented amphiphilic neoglycolipids forming liposome nanoparticles is reported. The small library was readily obtained from various peracetylated propargyl glycopyranosides via efficient radical-initiated thiol–yne (TYC) coupling reactions using alkanethiols of different chain lengths. In addition, using sequential thiol–yne, both the nature and positioning of the lipophilic alkanethiols could be varied at will, thus providing unparalleled variability within the glycolipid structures. Two different classes of self-assemblies were prepared from the new neoglycolipids. First, liposomes of 150–300 nm were obtained by solvent injection of their ethanol or tetrahydrofuran (THF) solution in water. The resulting structures were analyzed by dynamic light scattering (DLS) and atomic force microscopy (AFM). The mannosylated lipid nanoparticle (compound14 ) showed good stability in water. Alternatively, giant soft unilamellar vesicles were also obtained by film hydration and visualized by differential interference contrast microscopy (DIC). Incorporation of a hydrophobic dye to the solution prior to evaporation allowed visualization by confocal microscopy. Finally, the biological functions of the newly formed glycolipid vesicles were evaluated by multivalent carbohydrate–protein binding interactions using concanavalin A (ConA). Agglutination assays and the binding of glycolipid by dendritic cells (DCs) resulted in an increase in DCs immunostimulatory potential. Importantly, we did not see changes in cells viability at tested doses. This study provides a new, simple and highly efficient methodology to produce novel glyconanoparticle candidate as model in development of vaccine adjuvant and drug delivery system.